Nucleic acid aptamer application in diagnosis and therapy of colorectal cancer based on cell-SELEX technology. Issue 1 (December 2017) - Chen, Chan; Zhou, Shan; Cai, Yongqiang; Tang, Faqing
Abstract Nucleic acid aptamers are a class of high-affinity nucleic acid ligands. They serve as "chemical antibodies" since their high affinity and specificity. Nucleic acid aptamers are generated from nucleic acid random-sequence using a systematic evolution of ligands by exponential enrichment (SELEX) technology. SELEX is a process of effectively selecting aptamers from different targets. A newly developed cell-based SELEX technique has been widely used in biomarker discovery, early diagnosis and targeted cancer therapy, particular at colorectal cancer (CRC). Combined with nanostructures, nano-aptamer-drug delivery system was constructed for drug delivery. Various nanostructures functionalized with aptamers are highly efficient and has been used in CRC therapeutic applications. In the present, we introduce a cell- SELEX technique, and summarize the potential application of aptamers as biomarkers in CRC diagnosis and therapy. And some characteristics of aptamer-targeted nanocarriers in CRC have been expatiated. The challenges and perspectives for cell-SELEX are also discussed.